Randomized clinical trial of postoperative chewing gum versus standard care after colorectal resection. Issue 8 (5th May 2016) - Atkinson, C.; Penfold, C. M.; Ness, A. R.; Longman, R. J.; Thomas, S. J.; Hollingworth, W.; Kandiyali, R.; Leary, S. D.; Lewis, S. J.
Abstract: Background: Chewing gum may stimulate gastrointestinal motility, with beneficial effects on postoperative ileus suggested in small studies. The primary aim of this trial was to determine whether chewing gum reduces length of hospital stay (LOS) after colorectal resection. Secondary aims included examining bowel habit symptoms, complications and healthcare costs. Methods: This clinical trial allocated patients randomly to standard postoperative care with or without chewing gum (sugar‐free gum for at least 10 min, four times per day on days 1–5) in five UK hospitals. The primary outcome was LOS. Cox regression was used to calculate hazard ratios for LOS. Results: Data from 402 of 412 patients, of whom 199 (49·5 per cent) were allocated to chewing gum, were available for analysis. Some 40 per cent of patients in both groups had laparoscopic surgery, and all study sites used enhanced recovery programmes. Median (i.q.r.) LOS was 7 (5–11) days in both groups ( P  = 0·962); the hazard ratio for use of gum was 0·94 (95 per cent c.i. 0·77 to 1·15; P = 0·557). Participants allocated to gum had worse quality of life, measured using the EuroQoL 5D‐3L, than controls at 6 and 12 weeks after operation (but not on day 4). They also had more complications graded III or above according to the Dindo–Demartines–Clavien classification (16 versus 6 in the group that received standard care) and deaths (11 versus 0), but none was classed as related to gum. No other differences were observed. Conclusion: Chewing gum did not alter the return of bowel function or LOS after colorectal resection. Registration number: ISRCTN55784442 (http://www.controlled-trials.com ). Abstract : No advantage observed